Ação antrópica, pobreza e degradação dos recursos naturais no Maranhão: o caso do município de Rosário - Lindoso, Jane Carla Garcia (2003)
The county of Rosario is situated in the left side of Itapecuru River, and is located at meddle region of Maranhão North. This river contains various courses of water, forest species, and it contains a very diversity of animals. This one of the poorest region in Maranhão State, and is experiencing a very high process of deprivation of it natural resources. This results in large areas of rare and secondary forests. In this natural environment that families look for their survival. The county is also characterized by the elevated number of very small farms that we call minifúndios, and landless or no owners of the lands they work on. In this study we try to find out information in order to construct a diagnosis the principal causes of this degradation stage of natural resources in Rosário, as well to find out the principal causes of the very high level of poverty which is the portrait of those family living both in rural and urban areas of this county. This research took place in urban and rural area of Rosário and we used both structured and non structures instruments to catch out the relevant information. Doing so, we constructed a random sample of 223 families, which live in 18 small places in urban area and rural area of Rosario. The majority of families are excluded from the public politics, like basic services as safe water, sanitation and so on. The large number of people living in each family (the average is 7 people per family), and the limited areas the families in rural area livre (3 hectares in average per family) has caused a very high effectover the natural resources, wich contributed to increase the devastation process of those natural resources. The principal agricultural activities are: rice, cassava, bean and corn. Those activities are associated with the cultivation of small animals like pigs and chicken. The trading of the cassava products is the principal source of income for those poor families, who survive without services like public health, education, sanitation and shelter. The form of cultivation of the agricultural products are based in the use of fire in order to clean the dfeas. So they have small chances to grow up, and the other sources of income are activities like small industries, hand activities, and the use of natural soil to make the things they use as sources of work and income. In doing so, they increase the degradation of the environment. In this context the study suggest the use of public politics in order to increase the rural development in those areas, making enforcement to increase the food security, working activities and income, and preserve and give back the previous conditions of environment